Prevalence of Gastroesophageal Reflux Disease in Type II Diabetes Mellitus - Huihui Sun; Lisha Yi; Ping Wu; Yingjie Li; Bin Luo; Shuchang Xu (Gastroenterology Research and Practice)
Background/Aims. Patients with type II diabetes mellitus (DM) were known to have higher prevalence of gastroesophageal reflux disease (GERD) in the Western countries, but data on the impact of GERD on DM patients in our country are scarce. The aim of this study was to evaluate the prevalence of GERD in type II DM patients in Shanghai, China, and to explore its possible risk factors. Methods. 775 type II DM cases were randomly collected. Reflux Disease Questionnaire (RDQ) was used to check the presence of GERD. Patients’ characteristics, laboratory data, face-to-face interview, nerve conduction study, and needle electromyogram (EMG) test were analyzed. Results. 16% patients were found with typical GERD symptoms. Pathophysiological factors such as peripheral neuropathy, metabolism syndrome, and obesity were found to have no significant differences between GERD and non-GERD type II DM patients in the present study. Conclusion. The prevalence of GERD in type II DM patients is higher than that in adult inhabitants in Shanghai, China. No difference in pathophysiological factors, such as peripheral neuropathy, and metabolism syndrome was found in DM-GERD patients, suggesting that further study and efforts are needed to explore deeper the potential risk factors for the high prevalence rate of GERD in DM patients.